2020
DOI: 10.1021/acssynbio.0c00264
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring Central Carbon Metabolism Ensures Increased Provision of Acetyl-CoA and NADPH Required for 3-OH-Propionic Acid Production

Abstract: The central carbon metabolite acetyl-CoA and the cofactor NADPH are important for the synthesis of a wide array of biobased products. Here, we constructed a platform yeast strain for improved provision of acetyl-CoA and NADPH, and used the production of 3-hydroxypropionic acid (3-HP) as a case study. We first demonstrated that the integration of phosphoketolase and phosphotransacetylase improved 3-HP production by 41.9% and decreased glycerol production by 48.1% compared with that of the control strain. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…Streamlining sugar utilization through the use of this carbon-conserving pathway has the potential of increasing maximum theoretical yields for AcCoA-derived products in biotechnological applications [23][24][25]. Such a strategy has been harnessed both in bacteria and yeast, most often as an additional route to the linear EMP glycolysis [2,26,27]. The question is whether a synthetic PKT metabolism can be implanted in P. putida to boost AcCoA levels-but such a goal entails a radical rewiring of the metabolic connections that lead to AcCoA formation in this obligate aerobe [28] that runs a cyclic, ED-based sugar catabolism [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Streamlining sugar utilization through the use of this carbon-conserving pathway has the potential of increasing maximum theoretical yields for AcCoA-derived products in biotechnological applications [23][24][25]. Such a strategy has been harnessed both in bacteria and yeast, most often as an additional route to the linear EMP glycolysis [2,26,27]. The question is whether a synthetic PKT metabolism can be implanted in P. putida to boost AcCoA levels-but such a goal entails a radical rewiring of the metabolic connections that lead to AcCoA formation in this obligate aerobe [28] that runs a cyclic, ED-based sugar catabolism [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Acetyl-CoA is a direct precursor of OAH biosynthesis, and a very key intermediate metabolite and regulator in organisms [ 38 ]. Therefore, the effective supply of acetyl-CoA should be an important factor for the efficient production of OAH.…”
Section: Resultsmentioning
confidence: 99%
“…The PPP pathway and TCA cycle are known to be the major sources of NADPH regeneration in organisms, and glucose 6-phosphate dehydrogenase (ZWF) and 6-phosphogluconate dehydrogenase (GND) are key enzymes involved in NADPH synthesis. Studies have shown that overexpression of zwf and/or gnd can significantly increase the availability of intracellular NADPH [ 16 , 42 ]. In this study, the native promoter of zwf in the recombinant strain BS008 was replaced with the constitutive strong promoter P hbs , resulting in the attainment of the strain BS010.…”
Section: Resultsmentioning
confidence: 99%